Computer Vision Projects with OpenCV and Python 3 : Six end-to-end projects built using machine learning with OpenCV, Python, and TensorFlow /: Six end-to-end projects built using machine learning with OpenCV, Python, and TensorFlow. (2018) - Rever, Matthew
No abstract available